PEMBELAJARAN IPA BERBASIS KONSELING UNTUK MEMBENTUK PEMAHAMAN TENTANG PUBERTAS PADA SISWA SEKOLAH DASAR - Setyo Eko Atmojo (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2014)
The purpose of this study was to determine whether reproductive learning-based counseling can form a true understanding of puberty and reproduction in elementary school children. The subjects were sixth grade students at three elementary schools representing urban, middle and periphery. The analysis showed 85% of urban elementary school students, 87% middle school students and 92% suburban elementary students have had knowledge of puberty and reproduction.